2018
DOI: 10.1136/inp.k435
|View full text |Cite
|
Sign up to set email alerts
|

Understanding feline idiopathic cystitis

Abstract: Feline idiopathic cystitis is a common disease of unknown aetiology. Despite numerous studies, our understanding of this disease remains poor and although there are some interesting and attractive theories about the pathogenesis of the disease, much remains to be confirmed. Along with our poor understanding of the pathogenesis of disease, knowledge of effective therapeutic intervention is also rudimentary. This article explores the current state of knowledge of these aspects of the disease and takes an evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…These findings are consistent with Buffington (2002) and Lew-Kojrys et al (2017), who identified sedentary behaviour as a significant risk factor for feline idiopathic cystitis which could result in urethral obstruction. All tom cats were fed with commercial feed and had lower water intake and these findings were in accordance with Segevet al (2011), Cooper (2015) and Sparkes (2018). History revealed previous incidence of uropathy in 50 per cent of the animals and Saevik et al (2011) also observed that 37.6 per cent of cats suffered from previous episodes of FLUTD.…”
Section: Resultssupporting
confidence: 87%
“…These findings are consistent with Buffington (2002) and Lew-Kojrys et al (2017), who identified sedentary behaviour as a significant risk factor for feline idiopathic cystitis which could result in urethral obstruction. All tom cats were fed with commercial feed and had lower water intake and these findings were in accordance with Segevet al (2011), Cooper (2015) and Sparkes (2018). History revealed previous incidence of uropathy in 50 per cent of the animals and Saevik et al (2011) also observed that 37.6 per cent of cats suffered from previous episodes of FLUTD.…”
Section: Resultssupporting
confidence: 87%
“…The significance of the effects of stress in cats has been increasingly recognised in recent years, with stress affecting general well-being and potentially putting cats at increased risk of certain health problems, such as infectious diseases, feline lower urinary tract disease, 1 and behavioural problems such as over-grooming and urination/defecation outside the litter box. Their cat being stressed, and its associated behaviour changes, can have an impact on owners too, with the 2020 PDSA Animal Wellbeing report 2 finding that 41% of owners wanted to change a behaviour potentially linked to stress in their cat.…”
Section: Introductionmentioning
confidence: 99%